(untitled) (SCIÉNDO INGENIUM, 2024)
There are four known methods to treat solutions with high cyanide content: natural degradation, chemical oxidation, precipitation and biological degradation. This research is carried out within the framework of chemical oxidation, with the objective of demonstrating the detoxification of cyanide with hydrogen peroxide; and having copper as a catalyst in cyanide solutions. The effect of copper concentrations of 4 was evaluated; 5; 6 and 7 ppm to reduce the levels of free cyanide in the effluent solutions of a mining plant. The average cyanide concentrations of the solutions at the inlet and outlet were reported, concluding that the copper concentration of 7 ppm obtained the best results, reducing cyanide levels from 48.31 ppm to 0.018 ppm; which is within the Maximum Permissible Limits (MPL) given by the MINAM, which corresponds to 0.8 mg/L on an annual average and 1 mg/L at any time.